Dispersion in slurry shield tunnelling. Issue 4 (20th August 2020) - Weiner, Thorsten; Thewes, Markus
Abstract: In diesem Beitrag soll anhand von Projekterfahrungen sowie einer beispielhaften ökonomischen Betrachtung die Relevanz der Dispergierung für die Tunnelbaupraxis herausgestellt werden. Die Autoren empfehlen, den vor kurzem entwickelten Versuch zur Prognose der Dispergierung sowie den zugehörigen vertraglichen Mechanismus verstärkt anzuwenden. Abstract: In this contribution the relevance of dispersion for tunnel construction will be demonstrated on the basis of project experience and an exemplary economic consideration. The authors recommend application of the recently developed test for the prediction of dispersion as well as more intensive use of the corresponding contractual mechanism.